CARATTERI DIAGENETICI DEI CARBONATI DI PIATTAFORMA DEL TRIAS SUPERIORE NELL'APPENNINO MERIDIONALE E LORO IMPLICAZIONI PALEOGEOGRAFICHE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
The diagenetic features of two lithofacies assemblages found in the Upper Triassic of Lattari Mountains are illustrated. The first one, Norian in age, consists of cyclic dolomitic successions containing several horizons with synsedimentary antiform structures (tepee) and thick crusts of laminated cements, formed during early diagenesis. The second one, Rhaetian in age, is characterized by the striking abundance of laminated and radial fibrous (raggioni or giant rays) cements wirh respect to relict clasts of loferitic, calcareous-dolomitic former sediments. Moreover, it is emphasized that dolomitization patterns of Norian and Rhaetian age, respectively, are very different, which possibly reflects a global control. Similar Late Triassic facies outcrop in Maratea Mountains, underlaying a Meso-Cenozoic succession (Verbicaro Unit) considered transitional between the apenninic carbonate platform and a pelagic, basinal domain. Both these facies assemblages are interpreted as pertaining to a platform margin complex, frequently subjected to subaerial exposures and affected by strong early diagenetic processes. It is also hypothized that the adjacent basinal domain was located in a more westernly, "tyrrhenian" position. Finally, it is emphasized that the analysis of diagenetic features of Upper Triassic sequences might greatly help in paleoenvironmental and stratigraphic reconstructions and reveals a more complex paleogeography respect to previous and more traditional interpretations.
Keywords: Upper Triassic; Southern Italy; Apennines; carbonate platform; carbonate diagenesis; tepee; cement reef.